DETERMINING FACTORS AND INDICATORS FOR ALTERNATIVE MODEL OF NATIONAL SOYBEAN PRODUCTION ENHANCEMENT - NELLY B.; PRATIKTO; SUDJITO S; PURNOMO B. SANTOSO (Journal of Engineering Science and Technology, 2017)
This research surveys, interviews and Questionnaire were conducted by relevant agencies. Data was analyzed by calculating the cumulative frequency distribution and the average value (Mean) to 5 Likert scale, Validation, reliability, Pattern Model and Hypothesis were analyzed by SPSS 17 software for Windows. Validity model and the Measurement Model were examined by using Smart software PLS. The results show that the mean was 3.98 for Product Cost Appropriate and Stable Factor, 4.39 for High Productivity Factor, 4.36 for Enough Capital Factor, 3.73 for Character Farmers Factor, 4.28 for Information Access Factor, and 4.44 for High Production Factor. The data were valid and reliable. The relationship between the factors and indicators show strong correlation with an average of 0.96 with model pattern Quadratic and Cubic. Test Goodness of Fit model was fit. Hypothesis test results with five independent variables and one dependent variables were significant, excepted Character Farmers Factor and Information Access Factor were not significant to High Production Factor. Model was able to explain the phenomenon of high production by 91.7%, while the rest (8.3%) was explained by other variables not included in the model under studied. Enhancement production of national soybean would be affected dominantly by sufficient capital (97%).